Seismic performance of reinforced concrete frame buildings in Bhutan based on fuzzy probability analysis - Thinley, K.; Hao, Hong (Pergamon, 2017)
Seismic performance of reinforced concrete (RC) frame buildings is mostly assessed based on the distinct interstorey drift limits defined by many existing guidelines. In reality, damage of a structure is a continuous process under the action of the load and also depends on a number of factors. Therefore damage can be more logically defined with a fuzzy performance level than a distinct interstorey drift limit. In this paper, probability and fuzzy set theory are used to estimate the realistic failure probabilities of the RC buildings in Bhutan by considering randomness in material and geometrical parameters and fuzziness in the damage criteria. Three typical RC frame buildings in Thimphu, Bhutan and the ground motions predicted at the generic soil sites in Thimphu are used for the structural response prediction. Rosenbluth Point Estimate Method is used for modelling the statistical variation of the input parameters and the computer program Perform 3D is used for carrying out the dynamic nonlinear analysis of the buildings. Monte Carlo Simulation is employed to validate the accuracy of the Rosenbluth Point Estimate Method and determine the statistical distribution of the response quantities. Soil structure interaction (SSI) is considered at the soft soil site using the uncoupled spring model. Based on the mean and standard deviation of the intersotrey drifts obtained from the analyses, the fuzzy failure probabilities of the buildings are estimated. It is found that under the 475 year return period ground motions, typical buildings experience a high probability of irreparable and severe damages, while the high probability of severe damage and complete collapse are predicted under the 2475 year return period ground motions. SSI is found to be detrimental to the 3 storey building, while no significant effect is observed to the 6 storey building.